Effects of Musical Tempo on Musicians’ and Non-musicians’ Emotional Experience When Listening to Music - Liu, Ying; Liu, Guangyuan; Wei, Dongtao; Li, Qiang; Yuan, Guangjie; Wu, Shifu; Wang, Gaoyuan; Zhao, Xingcong (Frontiers in Psychology, 2018)
Tempo is an important musical element that affects human’s emotional processes during music listening. However, it remains unclear how tempo and musical training affect individuals’ emotional experience. To explore the neural underpinnings of the effects of tempo on music-evoked emotion, music with fast tempo, medium tempo, and slow tempo were collected to compare differences in the emotional responses and functional magnetic resonance imaging(fMRI) neural activity between musicians and non-musicians. Behaviorally, musicians perceived higher valence in fast music than non-musicians did. The main effects of group and tempo were significant, and a significant interaction between group and tempo was found. In the arousal dimension, the scores presented as Mmedium > Mfast and Mmedium > Mslow; in the valence dimension, the scores presented as Mfast > Mslow > Mmedium. Functional analyses revealed that the neural activation of musicians was stronger than non-musicians’ in the left inferior parietal lobe (IPL). A comparison of tempi showed that activation by fast music was stronger than slow music in bilateral superior temporal gyrus (STG), which provided the neural evidence for the highest valence in fast music. Activation by medium music was stronger than slow music in the right Heschl’s gyrus(HG), right middle temporal gyrus(MTG), right posterior cingulate gyrus(PCC), right precuneus, right IPL and left STG, which provided neural evidence of the medium music having the highest arousal and lowest valence. Importantly, the current study confirmed and explained the connection between music tempo and emotional experiences and their interaction with individuals’ musical training.